The potential of bitter melon extract on cellular non-specific immunity of koi fish (Cyprinus carpio) after Aeromonas salmonicida infection - SRI ANDAYANI; MOH. FADJAR; HENY SUPRASTYANI; AULIA RAHMAWATI; NURHALISA NURHALISA; VINA NUR NADIRO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Andayani S, Fadjar M, Suprastyani H, Rahmawati A, Nurhalisa, Nadiro VN. 2023. The potential of bitter melon extract on cellular non-specific immunity of koi fish (Cyprinus carpio) after Aeromonas salmonicida infection. Biodiversitas 24: 5215-5222. Indonesia has rich and potential fisheries resources both in freshwater (inland), coastal, and ocean. Potential fishery resources in freshwater include the diversity of fish species (germplasm) and fishery land. Utilization of freshwater fisheries potential can be realized by conducting fish farming, especially for economically valuable fish commodities, such as koi fish (Cyprinus carpio). Improving koi fish farming can be done by using bitter melon extract as an immunity enhancer. This study was conducted with the aim to determine the effect of bitter melon extract on cellular non-specific immune response. This study used a completely randomized design (CRD) method, with 4 treatments and 3 replicates, consisting of treatment K = not given bitter melon extract and not infected, A = dose of bitter melon extract 100 ppm, B = bitter melon extract 150 ppm, C = bitter melon extract 200 ppm. Before being given the treatment, the test fish were acclimatized with the aim of ensuring that the fish were healthy, not stressed and did not experience death. In addition, the dose of extract treatment and soaking time have been through the LD50 test as well as the density of bacterial infection and the length of time of infection have been through the LC50 test so that it has been confirmed that it does not cause stress and death in fish, with results SR 100%. A total of 10 fish were immersed into each treatment container (15 liters of water mixed with the extract) for 60 hours. Infection of Aeromonas salmonicida bacteria by immersion was carried out 5 days after immersion in bitter melon extract with a bacterial density of 107 cells.mL-1 for 1 hour. The results showed that lymphocytes increased after being given bitter melon extract and infected with A. salmonicida bacteria with a value of 63-83%. Monocytes increased from 3% to 8%, and Neutrophils increased from 4% to 9%. Phagocytosis activity increased from 18.4% to 28.9%, indicating that bitter melon extract can enhance non-specific immunity.